Rotary cutting test on rock-breaking mechanism and efficiency of milled-tooth rolling cutters for shaft sinking by drilling methods - Xiaoyun Wang; Hua Cheng; Jian Lin; Zhishu Yao; Longhui Guo; Liangliang Zhang (Scientific Reports)
Abstract To address the low rock-breaking efficiency of milled-tooth rolling cutters used for shaft sinking via drilling methods in the Jurassic strata of Western China, this study conducted rotational cutting tests using a mechanical rock-breaking test platform. The rock-breaking mechanisms and efficiency of the cutter were systematically investigated. First, rock-like material specimens were prepared based on the physical and mechanical properties of the weakly cemented sandy mudstone from the Jurassic system. Second, rotational cutting tests on Jurassic sandy mudstone-like materials were conducted on a mechanical rock-breaking test platform using a milled-tooth rolling cutter, a tool commonly employed in shaft sinking by drilling methods. Finally, the rock-breaking phenomena and modes of the milled-tooth rolling cutter were described in detail. Furthermore, the effects of penetration and rotational speeds on the rock-breaking force, cutting coefficient, rock drillability index, rock-breaking specific energy, and coarseness index were thoroughly discussed. The main findings are as follows. (1) The average rock-breaking force exhibited a positive linear correlation with both the penetration and rotational speeds of the rolling cutter. (2) When the penetration exceeded 1.5 mm and the rotational speed was below 0.19 rps, the drillability of the rock improved. (3) The milled-tooth rolling cutter achieved the highest efficiency at a penetration range of 2.0 and 3.0 mm. These findings could provide theoretical support for selecting rock-breaking cutting tools for shaft sinking by drilling methods in weakly cemented Jurassic strata in Western China and for optimizing the power parameters of drilling rigs under such conditions.